2020
DOI: 10.1037/apl0000437
|View full text |Cite
|
Sign up to set email alerts
|

Ethical champions, emotions, framing, and team ethical decision making.

Abstract: Research has offered a pessimistic (although limited) view regarding the effectiveness of ethical champions in teams and the social consequences they are likely to experience. To challenge this view, we conducted two multimethod (quantitative/qualitative) experimental studies in the context of entrepreneurial team decision-making to examine whether and how an ethical champion can shape team decision ethicality and whether ethical champions experience interpersonal costs. In Study 1, we found that confederate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 148 publications
2
42
0
2
Order By: Relevance
“…Entrepreneurship is widely perceived to be an "emotional rollercoaster" (Schindehutte et al, 2006) involving a range of positive and negative emotions (Fodor and Pintea, 2017). Although being an entrepreneur is experienced as satisfying (Benz and Frey, 2008;Morris et al, 2012;Stephan, 2018), entrepreneurs routinely face uncertainties, setbacks and challenges (van Gelderen, 2012). The negative emotions generated by the entrepreneurial process raise the question why and how surviving entrepreneurs are able to persist and even thrive under such conditions.…”
Section: Theoretical Motivation and Opportunities For Conceptual Devementioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship is widely perceived to be an "emotional rollercoaster" (Schindehutte et al, 2006) involving a range of positive and negative emotions (Fodor and Pintea, 2017). Although being an entrepreneur is experienced as satisfying (Benz and Frey, 2008;Morris et al, 2012;Stephan, 2018), entrepreneurs routinely face uncertainties, setbacks and challenges (van Gelderen, 2012). The negative emotions generated by the entrepreneurial process raise the question why and how surviving entrepreneurs are able to persist and even thrive under such conditions.…”
Section: Theoretical Motivation and Opportunities For Conceptual Devementioning
confidence: 99%
“…However, recent studies have shown that anxiety may also facilitate the creative thinking and effort of entrepreneurs (Foo et al, 2009;Cacciotti et al, 2016). Moreover, although anxiety is ubiquitous and negatively experienced, entrepreneurs express satisfaction with their work (Benz and Frey, 2008;Stephan and Roesler, 2010;Morris et al, 2012;Barba-Sánchez and Atienza-Sahuquillo, 2017). This suggests that persisting entrepreneurs are often able to harness anxiety and thrive in these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that framing of issues in either moral or economic terms impacts both the processes that individuals use to make ethical decisions and the outcomes that they pursue (Bazerman & Tenbrunsel, 2011; Tenbrunsel & Messick, 1999; Tenbrunsel & Northcraft, 2009). Recently, both Chen, Treviño, and Humphrey (2020) and Mayer, Ong, Sonenshein, and Ashford (2019) demonstrated that framing issues in moral terms can greatly influence issues’ acceptance, often times above and beyond the same issues sold in economic terms (Sonenshein, 2006), particularly if the moral frame is consistent with the organization's values and mission (Mayer et al., 2019).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…For example, frontline managers who perceive a stronger status in the organization may be more willing to speak up without the fear of retaliation ( Paterson and Huang, 2019 ). We need to examine this boundary condition and its influence on role expectancy behaviors because emerging research is starting to reshape how we approach the framing process of VBL behaviors (see Derfler-Rozin et al, 2016 ; Desai and Kouchaki, 2017 ; Yam et al, 2019 ; Chen et al, 2020 ). Thus, frontline managers’ willingness to voice and give voice is important to maintain their status and influence ( Bienefeld and Grote, 2014 ), because the existence of VBL behaviors is meant to foster an increase in similar patterned behaviors ( Kakkar et al, 2016 ).…”
Section: Boundary Conditions That Strengthen the Role Of Value-based Leadership Behaviormentioning
confidence: 99%